A Research Study on Effect of Diabetes, Awareness, Guideline and its Treatment - Samreen Kishwar Abbasi, Abdulfattah Omar, Talha Shabbir, Kalim Ullah, Ambreen Tauseef, Sidra Masood, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Diabetes is considered as the major disease which is increasing day by day in world wide. Research shown that it should be properly treated and routine visits to doctors are needed to overcome this issue, otherwise it will lead to major cause and severe health issues. Methods: To check out the actual results, they collect different samples from different clinics of Lahore. They were trying to check out the self-check from patients. Interviews has taken by face to collect certain data. Results: After taking interviews, they collect results as the ages of people suffering from diabetes was between 55-65 years. Patients suffering with type 2 diabetes were about 390 and people who suffers with type 1 diabetes was 80. Glucose in the blood was about 9.03 moll/l. Conclusion: If patients are suffering from type 2 diabetes, they should have proper self-awareness, effectiveness of their treatment, self-efficiency etc. Keywords: Diabetes mellitus, self efficiency, effectiveness, DSM, Type 2 diabetes.